Uranium cycle and tectono-metamorphic evolution of the Pan-African orogenic belt (Zambia) - (:unkn) unknown (My University, 2013)
Uranium is an incompatible and lithophile element and can be used as a geochemical tracer to discuss the generation and the evolution of continental crust. This thesis, focused on the Pan-African Lufilian belt in Zambia, characterizes the U cycle for this crustal segment. Silici-clastic and evaporitic sediments have been deposited within an intracontinental rift during the dislocation of the Rodinia supercontinent during the early Neoproterozoic. U-Pb ages on detrital zircon grains in these units indicate a dominant Paleoproterozoic provenance. The same zircon grains show subchondritic epsilonHf (between 0 and -15) and yield Hf model ages between ~2.9 and 2.5 Ga. These data suggest that the continental crust was generated before the end of the Archean associated with U extraction from the mantle. This old crust has been reworked by deformation and metamorphism during the Proterozoic. U has been remobilized and re-concentrated during several orogenic cycles until the Pan-African orogeny. During this Pan-African cycle, U-Pb and REY (REE and Yttrium) signatures of uranium oxides indicate a first mineralizing event at ca. 650 Ma during the continental rifting. This event is related to late diagenesis hydrothermal processes at the basement/cover interface with the circulation of basinal brines linked to evaporites of the Roan. The second stage, dated at 530 Ma, is connected to metamorphic highly saline fluid circulations, synchronous to the metamorphic peak of the Lufilian orogeny. These fluids are derived from the Roan evaporite dissolution. Some late uranium remobilizations are described during exhumation of metamorphic rocks and their tectonic accretion in the internal zone of the Lufilian orogenic belt
Keywords: African Research